Correlation between Quality of Nutritional Workers Services and Patient’s Satisfaction in Nutritional Services for Inpatient at Kajen General Hospital of Pekalongan District - Eko Wigiantoro; Martha Irene Kartasurya; Cahya Tri Purnami (Jurnal Manajemen Kesehatan Indonesia, 2013)
Pelayanan petugas gzi pada pasien rawat inap kelas III di RSUD Kajen Kabupaten belum sesuai harapan karena masih ada ketidakpuasan pasien/ keluarga pasien dalam hal pemberian makan yang tidak tepat waktu, tampilan makanan tidak menarik dan pelayanan petugas gizi yang kurang peduli, kurang tanggap dan kurang ramah. Penelitian ini bertujuan untuk mengetahui hubungan persepsi tentang mutu pelayanan petugas gizi dengan kepuasan pasien dalam pelayanan gizi di rawat inap kelas III. Jenis penelitian adalah survei analitik dengan pendekatan cross sectional. Pengumpulan data dilakukan dengan wawancara terstruktur. Variabel bebas adalah persepsi kehandalan, ketanggapan, jaminan, empati dan bukti langsung, variabel terikat adalah kepuasan pasien dalam pelayanan gizi. Jumlah sampel sebanyak 135 subjek diperoleh dengan teknik consecutive sampling. Analisis data menggunakan analisis korelasi Spearman Rank untuk analisis bivariat dan regresi linier ganda untuk analisis multivariat. Hasil penelitian menunjukan 59,3% persepsi kehandalan, baik, 61,5% ketanggapan, baik, 56,3% jaminan,, baik, 50,4% empati baik dan 65,2 % bukti langsung, baik serta 58,5% persepsi kepuasan, puas terhadap pelayanan gizi. Hasil analisis bivariat menunjukan bahwa ada hubungan yang signifikan antara kehandalan, ketanggapan, jaminan, empati dan bukti langsung terhadap kepuasan pasien dalam pelayanan gizi (p < 0,05 ). Hasil analisis mulitvariat menunjukan faktor yang berpengaruh paling kuat terhadap kepuasan pasien adalah persepsi bukti langsung (B=0,230). Disarankan kepada manajemen rumah sakit untuk meningkatkan pembinaan, pelatihan custumer service pada petugas gizi Nutritionist services to third-class inpatients in Kajen district general hospital (RSUD) of Pekalongan district were not according to what was expected. This was cause by unsatisfaction of patients or their family members regarding: meals that were not served in time; meal presentation that was not interesting; and nutritional staffs who did not care, were not responsive, and were unpolite. Objective of this study was to identify association between perception on service quality of nutritional staffs and patient satisfation toward nutritional service in the third-class inpatient rooms.  This was an analytical survey with cross sectional approach. Data were collected through interview guided by structured questionnaire. Independent variables were perception on validity, responsiveness, assurance, emphaty, and direct evidences. Dependent variable was patient satisfactory toward nutritional services. The number of study samples was 135 subjects selected using consecutive sampling. Data analysis was done by applying Spearman Rank correlation for bivariate analysis, and by applying multiple linier regression for multivariate analysis. Results of the study showed that 59.3% of respondent’s perception on validity were good; 61.5% of respondent’s perception on responsiveness were good; 56.3% respondent’s perception on assurance were good; 50.4% respondent’s perception on empathy were good, 65.2% of respondent’s perception on direct evidence were good; and 58.5% of respondent’s satisfaction were satisfactory toward nutritional service. Results of bivariate analysis showed significant associations between patient satisfaction toward nurtritional service and validity, responsiveness, assurance, empathy, and direct evidence (p< 0.05). Result of multivariate analysis showed that the most influencing factor toward patient satisfaction was perception on the direct evidence (B= 0.230). Hospital management is suggested to improve customer service assistance and training to nutritional staffs.